Correlations between Online Learning Media Types, First Access Time, Access Frequency, and Students’ Achievement in a Flipped Classroom Implementation - Daniel Febrian Sengkey; Sary Diane Ekawati Paturusi; Alwin Melkie Sambul (Faculty of Computer Science Universitas Indonesia, 2021)
Since the 1960s, the world has seen how Information Technology (IT) influences education. In the present era, with the massive development of the Internet, various kinds of IT-assisted learning are popping up like mushrooms in the rainy season. However, no matter how advanced IT-assisted learning has been grown, learning media is still an inseparable part of education. In this study, we specifically present how the use of certain types of learning media correlated with students’ access behaviors and, more importantly, students’ achievement. The result shows that these factors have a positive correlation. In terms of media type influence towards students’ achievement, the media that has the appearance of the lecturer gives better achievement, compared to the media that only has audio, and the media that only consists of text and images.